Monitoring Environment Safety Control Automation for Coalmine based on WSN-IoT - Kirubakaran, J.; Mathivanan, D.; Arunkumar, M.; Arulmurugan, M.S (Journal of ISMAC, 2024)
Miners' safety is indeed a critical issue, encompassing various challenges that put their health and lives at risk. Mining processes often emit hazardous and toxic fumes, posing serious risks to the health and safety of workers involved in these operations. This issue places significant strain on the mining industry, as it must continually work to mitigate these risks and ensure the well-being of its workforce. The research focuses on detecting temperature, fire, and harmful gases in coal mines using sensors in a Wireless Sensor Network (WSN) module. The detected data is then transmitted through a serial interface and sent to the corresponding location through the IoT cloud using Zigbee. The device provides an early warning system that assists miners in saving their lives before any fatalities occur. This is achieved through the establishment of a wireless sensor network using IoT technology. The proteus tool is used for designing the proposed work.
Keywords: Temperature Sensor; Zigbee; Wireless Sensor Node